1980
DOI: 10.1111/j.1365-3059.1980.tb01196.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of lettuce big‐vein disease by soil sterilisation

Abstract: SUMMARY Lettuce plants grown in the glasshouse in big‐vein‐contaminated soil previously treated with methyl bromide at 125–2000 kg/ha (x 0.125– 2.0 the dose used in the field) did not develop big‐vein symptoms, although at dosages up to 500 kg/ha their roots were infected by Olpidium brassicae(Wor.) Dang., the vector of the disease. Soil treatment with dazomet, chloropicrin, 1, 3‐dichloropropene or metham sodium gave symptom‐free plants at doses corresponding to those normally applied in the field. When applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…Bromide residues in lettuce heads at the first harvest after methyl bromide treatment were almost double those in an earlier experiment (White, 1980), although even the higher values were lower than some reported in papers reviewed by Hoffmann & M,alkomes (1979). It is possible that the cooler, wetter conditions encountered by this crop permitted increased uptake of bromide ions.…”
contrasting
confidence: 49%
See 3 more Smart Citations
“…Bromide residues in lettuce heads at the first harvest after methyl bromide treatment were almost double those in an earlier experiment (White, 1980), although even the higher values were lower than some reported in papers reviewed by Hoffmann & M,alkomes (1979). It is possible that the cooler, wetter conditions encountered by this crop permitted increased uptake of bromide ions.…”
contrasting
confidence: 49%
“…Pievious experiments (White, 1980) showed that the lettuce big-vein disease could be eliminated from soil contaminated with the big-vein vector Olpidium brassicae (Wor.) Dang, if treated with methyl bromide at 750 kg/ha.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Injection of methyl bromide into contaminated field soils has been successfully used to control big-vein disease of lettuce, which is transmitted by Olpidium brassicae (White, 1980(White, , 1983Campbell et al, 1980). The disease may also be controlled by incorporating carbendazim (methyl-2-yl-benzimidazole carbamate) into peat-blocks used for lettuce transplants, prior to transplanting in big-vein contaminated soil (White, 1983).…”
Section: Fungal Vectorsmentioning
confidence: 99%